{The Lavrion Mines : A Unique Site of Geological and} - Voudouris, Panagiotis; Melfos, Vasilios; Mavrogonatos, Constantinos; Photiades, Adonis; Moraiti, Eugenia; Rieck, Branko; Kolitsch, Uwe; Tarantola, Alexandre; Scheffer, Christophe; Morin, Denis; Vanderhaeghe, Olivier; Spry, Paul G.; et al. (Minerals, 2021)
The Lavrion area corresponds to the western part of the Attic-Cycladic metamorphic belt, in the back-arc region of the active Hellenic subduction zone. Between the Eocene and the Miocene, metamorphic rocks (mainly marbles and schists) underwent several stages of metamorphism and deformation due to collision and collapse of the Cycladic belt. Exhumation during the Miocene was accommodated by the movement of a large-scale detachment fault system, which also enhanced emplacement of magmatic rocks, leading to the formation of the famous Lavrion silver deposits. The area around the mines shows the stacking of nappes, with ore deposition mainly localized within the marbles, at marble-schist contacts, below, within, or above the detachment. The Lavrion deposit comprises five genetically-related but different styles of mineralization, a feature never observed in another ore deposit elsewhere, containing the highest number of different elements of any known mining district. The local geology, tectonic, and magmatic activity were fundamental factors in determining how and when the mineralization formed. Other key factors, such as the rise and the fall of sea level, which resulted from climate change over the last million years, were also of major importance for the subsequent surface oxidation at Lavrion that created an unmatched diversity of secondary minerals. As a result, the Lavrion deposit contains 638 minerals of which Lavrion is type-locality for 23 of them, which is nearly 12% of all known species. Apart from being famous for its silver exploitation, this mining district contains more minerals than any other district on Earth.